PN acquisition for DS - Delva, J.G.R.
An acquisition method of long pseudo-noise (PN) sequences in direct-sequence spread spectrum (DS/SS) systems is presented. The concurrent cross correlation of locally generated auxiliary signals with the incoming PN sequence produces binary search estimates leading to an initial approximation of the input signal's PN offset. The PN receiver then uses a closed-loop subsystem to determine the true offset of the incoming PN signal. New phase estimates are generated from successive corrections of likely errors in the binary search. The acquisition scheme's average acquisition time and its variance are analytically determined. Simulation results show that the proposed acquisition scheme is faster than the conventional serial receiver. A hybrid serial/parallel PN acquisition receiver is used for comparing the acquisition performance given similar hardware complexity. The hybrid receiver used the same number of parallel correlators as used in the proposed receiver's input phase estimator. Simulation results show that the proposed system provides an improved performance under normal operating conditions.
Keywords: Auxiliary signal; Closed loop selective search subsystem; Concurrent cross correlation; Direct-sequence spread spectrum system; Hybrid serial/parallel pseudonoise receiver; Preloop parallel binary search phase estimator; Pseudonoise acquisition